Effectiveness of PBL Models Assisted by Interactive Video on Problem-Solving Abilities of Elementary School Students (Journal of Primary Education, 2019)
The purpose of this study was to analyze the effectiveness of PBL models assisted by interactive videos on students' problem-solving abilities. The type of research used was quantitative research with the design of the control group pre-test post-test. The study population consisted of all fourth-grade students in the Kartini Group of Kudus City. The sample was selected through a purposive sampling technique so that the fourth grade of Elementary School Glantengan was selected which amounted to 27 students as the experimental group and fourth-grade Elementary School 4 Panjunan which amounted to 29 students as the control group. Data collection techniques use test techniques. The results of this study indicate that the classical completeness of the problem-solving ability of the experimental class reaches 92.5% with an average value of 83.52. The results of the analysis of problem-solving abilities in the experimental class showed that the indicator of understanding the problem had increased from 54% to 83%. The indicator for planning has increased from 56% to 82%. The indicator of solving problems has increased from 59% to 80%. The checking indicator has increased from 58% to 81%. The experimental class N-gain score scores reached 0.62 with a moderate category.